Vascular Imaging of the Head and Neck - Jadhav, Ashutosh P.; Jovin, Tudor G. (Seminars in Neurology, 2012)
Pathologies of the cranial and cervical vasculature are often devastating and require rapid and accurate anatomic delineation. The clinical scenario will often dictate the most appropriate imaging modality warranted. In this review, we will discuss the application of magnetic resonance angiography (MRA), computed tomographic angiography (CTA), and digital subtraction angiography (DSA) in the evaluation of cerebrovascular diseases with an emphasis on ischemic and hemorrhagic stroke. Noninvasive modalities such as MRA and CTA are becoming widely available and increasingly sensitive for most pathologies, but DSA continues to be the gold standard in cases of diagnostic ambiguity and is increasingly utilized with advances in endovascular treatments.
Keywords: stroke; dissection; carotid stenosis; vasculopathy; hemorrhage; aneurysm; arteriovenous malformation; magnetic resonance angiography (MRA); computed tomographic angiography (CTA); digital subtraction angiography (DSA)